2020
DOI: 10.1101/2020.05.14.096115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-canonical autophagy drives alternative ATG8 conjugation to phosphatidylserine

Abstract: 29 30 Autophagy is a fundamental catabolic process essential for development, 31 homeostasis and proper immune function 1 . During autophagy, a cascade of 32 ATG proteins target intracellular cargoes for lysosomal degradation and 33 recycling 2 . This pathway utilises a unique post-translational modification, the 34 conjugation of ATG8 proteins to phosphatidylethanolamine (PE) at 35 autophagosomes, which modulates cargo selection and maturation. 36 ATG8 lipidation also occurs during non-canonical autophagy, a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…We have shown that LC3 can also become conjugated to phosphatidylserine (PS)-enriched membranes during non-canonical autophagy. ATG4D, but not the other paralogues, appears to be uniquely capable for the de-conjugation of LC3-PS (Durgan et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that LC3 can also become conjugated to phosphatidylserine (PS)-enriched membranes during non-canonical autophagy. ATG4D, but not the other paralogues, appears to be uniquely capable for the de-conjugation of LC3-PS (Durgan et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations were made for GABAR-AP-L1 and GABARAP-L2. Elsewhere we describe a role for ATG4D in delipidation of phosphatidylserine conjugated LC3, which accumulates during WD40 CTD-dependent LC3-lipidation – including in response to IAV M2 – but not during canonical autophagy (Durgan et al, 2020). A missense mutation in ATG4D was found in Lagotto Romagnolo dogs with progressive neurological symptoms (Kyöstilä et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to LAP, LANDO requires Rubicon and ATG5 activity but not FIP200. Interestingly, a recent study has shown the ability of LC3 to be conjugated to another lipid, phosphatidylserine, expanding the possible roles of non-canonical autophagy pathways ( 41 ). Further studies are required to understand the role and the mechanism of these processes.…”
Section: Overview Of the Process Of Autophagymentioning
confidence: 99%
“…The evolved virus can take advantage of the autophagy proteins to construct its skeleton in the early stages of infection. ATG4B can hydrolytically cleave an EV71 3C pro substrate in addition to priming ATG8‐PE, ATG8‐PS, 16 and LC3B‐ATG3 187 . Therefore, further studies should be conducted on the novel functions of ATG4s as a cysteine protease.…”
Section: Atg4 and Diseasesmentioning
confidence: 99%
“…The C‐terminal residues of pro‐LC3 are immediately primed by a cysteine protease, ATG4B, producing the free cytoplasmic LC3‐I form and exposing a glycine at its COOH‐terminal. This renders the conjunction of LC3 with phosphatidylethanolamine (PE) on phagophore membranes mostly during canonical autophagy or alternatively to phosphatidylserine (PS) during noncanonical autophagy 13–16 . A succession of ubiquitin‐like proteins contributes to catalyzing the formation of an amide bond between the C‐terminal carboxyl group of LC3 and the hydrophilic head group amino of the lipid PE, producing covalent membrane‐bound LC3‐II 17,18 .…”
Section: Introductionmentioning
confidence: 99%